Adult Education and Development, 1993 - Hinzen, Heribert (Distributed by ERIC Clearinghouse, 1993)
These two issues of a half-yearly journal for adult education cover Africa, Asia, and Latin America. Number 40 consists of 35 articles on 4 themes: Multicultural dimensions; environmental learning; cooperation and partnership with Eastern Europe; and women and training. Articles include: "It Is Time to Understand that the World Belongs to All of Us" (Mane); "The Bensheimer Kreis Demands: Give Priority to Fighting the Causes for Large Refugee Movement!"; "Western Man--A Master of Detail But Blind to the Whole" (Willamo); "A Critical View of Environmental Education" (von Sanden, Evia); "Polish and German Coexistence" (Samlowski); "Adult Education in the Process of Rebuilding the Economy" (Marcinkiewicz); and "Systematizing Gender-Based Interventions: The Mindanao Experience" (Polestico). Number 41 consists of 22 articles on 3 major themes: indigenous peoples and learning; development and community participation; and adult education and training. Articles include: "What Is a True Indigenous School?: Indigenous Societies of Brazil and Their Schools" (Grupioni, Ferreira); "Literacy, Language, and the International Year for the World's Indigenous Peoples" (Brennan); "The Idiofa Peasant's Participation in Rural Development--A Lawsuit against the State" (Lowola); "To Collaborate in Order To Promote Laws in Rural Areas and Fight against Injustices"; (Mulunda, Ntashushwa); "What Brings about Changes in the Local Community" (Koineh); "Eradication of Illiteracy of Women and Girls in Vietnam" (Van); and "Expanding Training Delivery for Job Generation" (Gamerdinger). (YLB)